2013
DOI: 10.1158/1078-0432.ccr-12-3110
|View full text |Cite
|
Sign up to set email alerts
|

Weekly nab-Rapamycin in Patients with Advanced Nonhematologic Malignancies: Final Results of a Phase I Trial

Abstract: Purpose This dose-finding phase 1 study investigated the maximum tolerated dose (MTD) and safety of weekly nab-rapamycin in patients with untreatable advanced nonhematologic malignancies. Experimental Design nab-Rapamycin was administered weekly for 3 weeks followed by 1 week of rest, with a starting dose of 45mg/m2. Additional doses were 56.25, 100, 150, and 125 mg/m2. Results Of 27 enrolled patients, 26 were treated. Two dose-limiting toxicities (DLTs) occurred at 150mg/m2 (grade 3 AST elevation and grad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 54 publications
(65 reference statements)
1
31
0
Order By: Relevance
“…222 A phase I dose-finding study of q3 week ABI-009 in patients with advanced solid tumor malignancies was undertaken. 223 Dose was escalated from 45 to 125 mg/m 2 . Treatment was overall well tolerated.…”
Section: Protein Nanoparticlesmentioning
confidence: 99%
“…222 A phase I dose-finding study of q3 week ABI-009 in patients with advanced solid tumor malignancies was undertaken. 223 Dose was escalated from 45 to 125 mg/m 2 . Treatment was overall well tolerated.…”
Section: Protein Nanoparticlesmentioning
confidence: 99%
“…Biopolymer-based constructs (e.g. cyclodextrin CRLX-101) [11], mannose and diethylenetriaminepentaacetic acid 99m Tc-functionlised dextran [12] and proteins [13,14] are especially appealing because their inherent biodegradability renders them less likely to disrupt lysosomal function [3]. One important protein in this respect is silk, which has recently been proposed for use in drug delivery applications [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite showing good tolerability profiles when used alone or combined with other treatments, little anti-tumor activity has been reported in the clinic [ 40 , 41 , 42 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 ]. Efforts to improve the bioavailability and performance of these agents through nanoparticle encapsulation and binding are ongoing, although whether this improves their anti-tumor effects remains to be determined [ 250 , 251 ]. Nonetheless, early reports from a separate study have indicated promising responses in patients with PTEN-deficient mCRPC (NCT00976755).…”
Section: Targeting Pten-deficient Prostate Cancermentioning
confidence: 99%